Synthesis, Characterization, and Reactivity of Bivalent Tin(II) with 4-Tert-butylphenol - Kumari Bandna (International Journal of Photochemistry and Photochemical Research, 2024)
Bivalent tin(II)-4-tert. butylphenoxide of composition Sn(OC6H4X-4)2(I), where X = But, has been synthesized by the reaction of stannous chloride (SnCl2) with bimolar amounts of 4-tert. butyl phenol (HOC6H4But-4) in the presence of the base, diethyl amine, in tetrahydrofuran (THF) solvent. The resulting complex was characterized by elemental analysis, molecular weight determination, molar conductance measurement, IR, and 1H NMR spectral studies. The reactivity of the newly synthesized complex (I) with HgCl2 has been investigated using potentiometric techniques, followed by an actual reaction between the complex (Sn(OC6H4X-4)2) and mercuric chloride (HgCl2), resulting in the formation of a new Sn(IV) complex of composition SnCl2(OC6H4But-4)2. The quantitative formation of a grayish compound identified as Hg2Cl2 as a byproduct was observed. Elemental analysis of the solid compound isolated from the above solution corresponded well with its stoichiometric formulation as SnCl2(OC6H4But-4)2 and was later confirmed by molecular weight determination, conductance measurement, IR, and 1H NMR spectral studies. Conductometric titration between complex (I) and the sodium salt of 4-tert. butylphenol suggests the formation of a double phenoxide of composition Na2[Sn(OC6H4But-4)]4. Further investigations into the complex’s stability and potential applications in catalytic processes are underway, promising new insights into the behavior of tin(II) compounds in various chemical environments. This study enhances the understanding of the reactivity and complexation behavior of tin(II) with organic ligands, contributing to the broader field of coordination chemistry and its practical applications.
Keywords: 4-tert- butyl phenol; IR Spectra; NMR; Tin(II) phenoxide; reactivity